PRIMARY SCHOOL TEACHER CONSTRAINTS IN IMPLEMENTING THE INDEPENDENT CURRICULUM - Fransiska Jaiman Madu (Universitas Majalengka, 2025)
The independent curriculum builds teachers' enthusiasm for implementing learning that embraces the principle of diversity. The implementation is adapted to the local conditions. However, the fact is that the implementation of the independent curriculum is not as expected by the government. The obstacles teachers face are not few. This is due to the different situations in the field, including three primary schools in Kabupaten Manggarai, NTT. The teachers found obstacles, especially in the implementation of learning with the independent curriculum. This study aims to describe in detail the obstacles faced by primary school teachers in learning with the independent curriculum. This research uses qualitative approach and descriptive method. Three schools were selected because they have been implementing the Independent Curriculum for about two years. In addition, there are 12 respondents who are also implementing learning with the independent curriculum. The data collection technique used was in-depth interviews with the researcher as the main instrument. The data was analyzed using the steps of data collection, data reduction, data presentation, and conclusion. The results showed some of the main obstacles that elementary school teachers experienced in implementing learning with an independent learning curriculum, such as the preparation of learning tools, the implementation of assessments, the lack of student independence in learning, the limited time for teachers to learn, the ability of teachers to adapt teaching materials, and the limited training of teachers regarding the implementation of the independent learning curriculum.